Aplikasi Remote Sensing dan GIS untuk Pemetaan Perubahan Penggunaan Lahan dan Dampaknya Terhadap Persediaan Pangan di Kecamatan Denpasar Selatan - Rahmadani, Aditya; Lanya, Indayati; Bhayunagiri, Ida Bagus Putu (Agrotrop : Journal on Agriculture Science, 2024)
Application of Remote Sensing and GIS for Land Use Mapping and Impact on Food Supply in South Denpasar. The increasing demand for land, driven by population growth, societal development, and economic progress, leads to land use conversion. The conversion of agricultural land to non-agricultural purposes has implications for food availability. This research aims to assess land use changes over an 11-year period (2012-2023), determine the presence of subak (traditional Balinese irrigation system) in 2041 based on the Regional Spatial Plan (RTRW) map, and project the analysis of food availability in 2030 and 2040 due to land use changes. The methods employed include satellite image interpretation, digital mapping, map overlay, and food availability analysis. The research findings indicate land use changes from 2012 to 2018 resulted in a conversion of 140,66 hectares (23,44 ha/year), and from 2018 to 2023, a conversion of 18,8 hectares (3,76 ha/year), with a total conversion of 159,46 hectares (14,50 ha/year) from 2012 to 2023. Based on the RTRW spatial plan map for 2021-2041, South Denpasar is projected to potentially 4 subak located outside agricultural zones. Land use changes in South Denpasar have implications for the rice food balance, with a projected deficit of (-19.973) tons in 2030 and (-20.563) tons in 2040. Reevaluation of land use allocation policies is necessary due to their impact on food availability, environment, social, and culture.